Existence of a novel qepA variant in quinolone resistant Escherichia coli from aquatic habitats of Bangladesh - Rahman, Zillur (Gut Pathog, 2017)
Of 19 environmental Escherichia coli (n = 12) and Klebsiella pneumoniae (n = 7) tested for quinolone resistance-related genes qnrA, qnrB, qnrC, qnrS and qepA, four each of E. coli and K. pneumoniae possessed qnrS, and another E. coli isolate possessed a new variant of qepA. This is the first detection of qepA in environmentally dwelling bacteria in Bangladesh.